The relationship between weather and caribou productivity for the La-Poile Caribou Herd, Newfoundland - Steven H. Ferguson; Shane P. Mahoney (Rangifer, 1991)
To describe the relationship between weather and caribou (Rangifer tarandus) productivity, we compared weather variables (snow on ground, winter temperature and measures of growing season) with measures of productivity (calves seen by hunters, calves and yearlings in the harvest and percent calves and yearlings and pregnancy rate for caribou classified during fall and spring surveys) for the LaPoile Caribou Herd in southwestern Newfoundland. Hunter statistics reliably estimated changes in population demography. Percent calves seen by hunters was correlated with calves/100 females classified in fall. Weather may have influenced productivity for the LaPoile Caribou Herd in Newfoundland. Colder winter temperatures were associated with fewer calves the next fall and pregnancy rates and yearlings/100 females in the spring were negatively correlated with snow on ground the previous winter. These relationships appear to be density related.